2013
DOI: 10.5243/jsswr.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risk of Placement: A Population-based Study of Out-of-Home Placement, Child Maltreatment, and Emergency Housing

Abstract: Guided by a developmental epidemiology framework, this study examines the extent to which first experiences of child maltreatment and use of emergency housing are predictive of out-of-home placement in early childhood. The study sample is a population of 12,045 second-grade students in a large, urban school district. Information on birth, maternal, and social risk factors was obtained and linked through an integrated data system. Life table analyses were used to develop a descriptive picture of the timing of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…Compared with housed children, children experiencing homelessness are more likely to be involved with child protective service and have higher rates of substantiated maltreatment (Park, Metraux, Brodbar, & Culhane, 2004). In fact, Perlman and Fantuzzo (2013) found that almost 40% of children who had lived in emergency housing had experienced substantiated child abuse or neglect.…”
Section: Parenting Qualitymentioning
confidence: 99%
“…Compared with housed children, children experiencing homelessness are more likely to be involved with child protective service and have higher rates of substantiated maltreatment (Park, Metraux, Brodbar, & Culhane, 2004). In fact, Perlman and Fantuzzo (2013) found that almost 40% of children who had lived in emergency housing had experienced substantiated child abuse or neglect.…”
Section: Parenting Qualitymentioning
confidence: 99%
“…These histories of trauma and mental health diagnoses can impede parents' ability to respond sensitively and consistently to the needs of their children. Parents experiencing homelessness also experience higher rates of separation from their children, due to placement in foster or kinship care for extended periods of times (Barrow, Lawinski, 2009; Perlman & Fantuzzo, 2013). Cumulatively, these experiences result in significant disruptions in the parent-child relationship and negatively affect children's interactions with teachers and classmates.…”
Section: Discussionmentioning
confidence: 99%
“…When establishing a prevalence threshold for including a study, it was decided to include analyses of populations where all children were victims of CAN on the measures outlined above and populations of children in out‐of‐home care, known as looked after children (CLA) in England. Child maltreatment is the key factor, internationally, leading to children being separated from their birth families and placed in out‐of‐home care (Perlman & Fantuzzo, 2013). Out‐of‐home‐care populations contain a large proportion of children and young people who have experienced CAN.…”
Section: Methodsmentioning
confidence: 99%